The Implementation of Inquiry Method to Improve English Skills by Procedure Text Learning for Junior High School Students - Icha Triwiyanti; Sayyidati Maliha; Rizazah Putri Raudine; Leni Mardiah Napitupulu; Siti Ismahani; Malika Alya; Mahdia Arafah (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2023)
This article discusses the application of the inquiry method to improve English language skills in learning procedure texts for junior high school students. Procedure text provides step-by-step instructions for completing a task or process and plays an important role in language development. Inquiry methods that encourage active exploration, critical thinking, collaboration, and communication have proven to be effective approaches. By applying this method, students become active participants in the learning process, foster engagement and improve their language skills. This article highlights the benefits of applying inquiry methods, including enhanced language acquisition, development of critical thinking skills, and better communication. Practical strategies for implementation, such as pre-reading activities, guided and independent inquiry, and reflective discussions, are also provided. By incorporating the inquiry method, educators can empower students to become independent learners and improve their English skills through meaningful and contextual learning experiences.